Brain Microenvironment Responsive and Pro‐Angiogenic Extracellular Vesicle‐Hydrogel for Promoting Neurobehavioral Recovery in Type 2 Diabetic Mice After Stroke. Issue 22 (13th September 2022) - Jiang, Yixu; Wang, Ruiqi; Wang, Cheng; Guo, Yiyan; Xu, Tongtong; Zhang, Zhijun; Yang, Guo‐Yuan; Xu, He; Tang, Yaohui
Abstract: Stroke patients with diabetes have worse neurological outcomes than non‐diabetic stroke patients, and treatments beneficial for non‐diabetic stroke patients are not necessarily effective for diabetic stroke patients. While stem cell‐derived extracellular vesicles (EVs) show potential for treating stroke, the results remain unsatisfactory due to the lack of approaches for retaining and controlling EVs released into the brain. Herein, a glucose/reactive oxygen species dual‐responsive hydrogel showing excellent injectability, biocompatibility, and self‐healing capability is introduced as an EVs‐loading vehicle and an intelligent EVs sustained releasing system in the brain. These EVs‐hydrogels are developed via crosslinking of phenylboronic acid‐modified hyaluronic acid and Poly vinyl alcohol, and fusion with neural stem cell‐derived EVs. The results show EVs are stably incorporated into the hydrogels and can be controllably released in response to the brain microenvironment after stroke in type 2 diabetic mice. The EVs‐hydrogels exert an excellent angiogenic effect, increasing the migration and tube formation of human umbilical vein endothelial cells. In addition, injection of EVs‐hydrogels into the ischemic mouse brain enhances EVs retention and facilitates sustained release, promotes angiogenesis, and improves neurobehavioral recovery. These results suggest such a microenvironment responsive and sustained release EVs‐hydrogel system offers a safe, and efficient therapy for diabetic stroke. Abstract : The hydrogel is prepared via HA‐PBA coordination of PVA and then loaded with NSCs‐EVs. The NSCs‐EVs hydrogel is injected into the diabetic mouse at 24 h after stroke onset. The NSC‐EVs loaded hydrogel performed well in cell proliferation, migration and angiogenesis, and improved neurobehavioral recovery of diabetic mice after stroke.